Dehydrocostus Lactone Suppresses Dextran Sulfate Sodium-Induced Colitis by Targeting the IKKα/β-NF-κB and Keap1-Nrf2 Signalling Pathways - Yuan, Yun; Hu, Qiongying; Liu, Lu; Xie, Fan; Yang, Luyao; Li, Yuchen; Zhang, Chuantao; Chen, Hongqing; Tang, Jianyuan; Shen, Xiaofei (Frontiers in Pharmacology, 2022)
Dehydrocostus lactone (DCL) is a major sesquiterpene lactone isolated from Aucklandia lappa Decne, a traditional Chinese herbal medicine that used to treat gastrointestinal diseases. This study aimed to examine the therapeutic effects of DCL on dextran sulfate sodium (DSS)-induced colitis with a focus on identifying the molecular mechanisms involved in DCL-mediated anti-inflammatory activity in macrophages. First, oral administration of DCL (5-15 mg/kg) not only ameliorated symptoms of colitis and colonic barrier injury, but also inhibited the expression of proinflammatory cytokines and myeloperoxidase in colon tissues in DSS-challenged mice. Furthermore, DCL also exhibited significant anti-inflammatory activity in LPS/IFNγ-stimulated RAW264.7 macrophages. Importantly, DCL significantly suppressed the phosphorylation and degradation of IκBα and subsequent NF-κB nuclear translocation, and enhanced the nuclear accumulation of Nrf2 in LPS/IFNγ-treated RAW264.7 cells. Mechanistically, DCL could directly bind to IKKα/β and Keap1, thereby leading to the inhibition of NF-κB signalling and the activation of Nrf2 pathway. Furthermore, DCL-mediated actions were abolished by dithiothreitol, suggesting a thiol-mediated covalent linkage between DCL and IKKα/β or Keap1. These findings demonstrated that DCL ameliorates UC by targeting NF-κB and Nrf2 signalling, suggesting that DCL may be a promising candidate in the treatment of diseases harbouring abnormal NF-κB and Nrf2 signalling.